Peran Minat Beli dan Ekuitas Merek dalam Membentuk Keputusan Pembelian Mahasiswa - Lily Anggraeny Puspaningrum; Nadya Novia Rahman (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Ideally, students should be able to prioritize their needs; however, the transition to early adulthood often makes them more susceptible to emotional impulses when making purchasing decisions. This study aims to examine the effect of purchase intention and brand equity on purchasing decisions among students. The research subjects consisted of 75 students from the Faculty of Economics and Business, Mulawarman University, class of 2020-2022, selected using simple random sampling. Data were collected using purchase decision, purchase intention, and brand equity scales and analyzed using multiple linear regression. The results indicate that purchase intention and brand equity have a significant effect on purchasing decisions, as evidenced by an F value of 26.577, an R² value of 0.425, and a p value of 0.000. These findings support the acceptance of the main hypothesis, demonstrating that both variables play an important role in shaping students' purchasing decisions. The results also suggest that purchasing decisions are not solely driven by interest and brand value, but are influenced by cognitive, emotional, and evaluative factors in the consumer decision-making process. This study highlights the importance of enhancing purchase intention and strengthening brand equity as effective marketing strategies, while also contributing to the understanding of student consumer behavior.